2015
DOI: 10.1182/blood-2014-07-587170
|View full text |Cite
|
Sign up to set email alerts
|

The thrombopoietin receptor P106L mutation functionally separates receptor signaling activity from thrombopoietin homeostasis

Abstract: Key Points• The c-Mpl activity in downstream signaling and in platelet homeostasis can be functionally separated.• The c-Mpl platelet homeostasis depends on correct processing and surface expression of the receptor, whereas downstream signaling does not.The interaction between thrombopoietin (THPO) and its receptor c-Mpl regulates downstream cytokine signaling and platelet homeostasis. Hereditary mutations of c-Mpl can either result in loss-of-function and thrombocytopenia or in gain-of-function and thrombocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…Further biological studies should be afforded to exploit the CRLF2 pathway in T-ALL. Interestingly, it was recently reported in the literature that the activity of another cytokine receptor (cMPL) did not depend on its cell surface expression [31]. The authors assumed that the receptor with an abnormal subcellular distribution may be active and particularly sensitive to the low amount of ligand that may enter into the cell through trace levels of the receptor on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Further biological studies should be afforded to exploit the CRLF2 pathway in T-ALL. Interestingly, it was recently reported in the literature that the activity of another cytokine receptor (cMPL) did not depend on its cell surface expression [31]. The authors assumed that the receptor with an abnormal subcellular distribution may be active and particularly sensitive to the low amount of ligand that may enter into the cell through trace levels of the receptor on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, mild thrombocytosis was observed in heterozygous cases. Later on, it was reported that MPL P106L presents a defect in trafficking that prevents its translocation to the cell surface, but is still capable to bind TPO and to signal in the cytosol ( 62 ). This seems unlikely since the extracellular domain of MPL is localized in the lumen of endoplasmic reticulum.…”
Section: Effect Of Tpo/mpl/jak2 Axis Alterations In the Stimulation Omentioning
confidence: 99%
“…13 It is important to determine the functional impact of CAMT mutations on Mpl signaling and trafficking, because clinical presentation, disease progression, and treatment options reflect the underlying cellular mechanisms. 6,14,15 In this study, the severity of CAMT type I disease in 3 siblings was associated with a homozygous double MPL K39N/W272R mutant that resulted in complete blocking of Mpl trafficking to the plasma membrane. Currently, HSC transplantation is the only curative option for pediatric patients with life-threatening CAMT.…”
Section: Introductionmentioning
confidence: 71%
“…Since the first description of a disease-associated MPL mutation in CAMT in 1999, 1 more than 50 different genetic events have been reported for MPL, 2,3 and they are sometimes associated with defects in surface presentation. [4][5][6] Notably, the MPL Baltimore substitution (K39N) is associated with high platelet counts in patients of African American descent, despite incomplete processing and reduced Mpl protein levels. 7 Although cell surface expression of Mpl is required for stimulation by its ligand (Tpo), complex relationships between mutant and wildtype (WT) forms of Mpl, Jak2, and the endoplasmic reticulum (ER) chaperone calreticulin govern both the intracellular trafficking of receptors and signal propagation.…”
Section: Introductionmentioning
confidence: 99%